Mahasiswa Menuntut Keadilan: Mengurai Aksi Demonstrasi atas Kenaikan Tunjangan Anggota DPR dalam Perspektif Sosiologi Pendidikan - Karolus Teguh Santoso; Teresia Noiman Derung (Pusat Riset dan Inovasi Nasional, 2024)
This article discusses the phenomenon of student demonstrations against the policy of increasing allowances for members of the House of Representatives (DPR) through the perspective of the sociology of education. The allowance increase, perceived as a form of political elites’ insensitivity to the economic conditions of society, triggered a wave of student protests that regarded the policy as a symbol of structural injustice. This study employs a literature review method by examining academic literature, sociological theories, and relevant media reports. The analysis is conducted using the approaches of structural functionalism and conflict theory. From the functionalist perspective, student actions are understood as a response to social dysfunctions that disrupt societal stability, while conflict theory emphasizes the dimension of class struggle between political elites and the wider community. Education, in this context, plays a central role in shaping students’ critical awareness through curriculum, academic interactions, and organizational experiences that cultivate sensitivity to issues of social justice. Student demonstrations are not spontaneous reactions, but manifestations of an educational process that fosters critical and reflective thinking as well as the courage to challenge the status quo. This movement demonstrates that students serve as agents of change who not only advocate for public interests but also safeguard morality and the accountability of power. Thus, this phenomenon underscores the strategic role of higher education in producing a generation that is critically empowered and committed to democracy and social justice, while also highlighting that student actions hold significant relevance in maintaining the balance between the state, society, and academic ideals